2022
DOI: 10.1111/jog.15203
|View full text |Cite
|
Sign up to set email alerts
|

Threatened abortion, threatened premature labor, and preterm birth during the first state of emergency for COVID‐19 in 2020 in Japan

Abstract: Aim: This study examined the maternal experience of threatened abortion, threatened premature labor, or preterm birth before, during, and after the first state of emergency for COVID-19 in 2020 in Japan. Methods: This was a cross-sectional, internet-based questionnaire survey. We recruited 600 postpartum women and divided them into three groups by date of delivery: before (October 2019-March 2020), during (April-May 2020), and after (June-October 2020) the first state of emergency. The outcome was the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
2
9
1
Order By: Relevance
“…Our result is consistent with a previous report of decreased preterm birth during the pandemic in high-income countries 16 . Although another study also reported that the prevalence of TPL and preterm birth decreased during and after the state of emergency in Japan, we also demonstrated improved outcomes of neonatal complications based on a larger sample size compared to the previous study 17 . Furthermore, our study showed oral ritodrine hydrochloride usage in all the participants significantly decreased during the COVID-19 pandemic.…”
Section: Discussioncontrasting
confidence: 43%
“…Our result is consistent with a previous report of decreased preterm birth during the pandemic in high-income countries 16 . Although another study also reported that the prevalence of TPL and preterm birth decreased during and after the state of emergency in Japan, we also demonstrated improved outcomes of neonatal complications based on a larger sample size compared to the previous study 17 . Furthermore, our study showed oral ritodrine hydrochloride usage in all the participants significantly decreased during the COVID-19 pandemic.…”
Section: Discussioncontrasting
confidence: 43%
“…In this nationwide, cross‐sectional study, we used data of postpartum mother–infant pairs from the Japan COVID‐19 and Society Internet Survey (JACSIS) (https://jacsis-study.jp/). The JACSIS gathers data from the pooled panels of an internet research agency (Rakuten Insight, Inc. [https://insight.rakuten.co.jp/], which has approximately 2.3 million panelists currently); details of the JACSIS, quality controls, and other policies for panelists have been described previously 6,19,20 . Briefly, the JACSIS consists of three internet‐based survey panels of (a) young people and adults aged 15–79 years, (b) pregnant/postpartum mothers and fetus/infant pairs, and (c) adults living in a single‐parent household.…”
Section: Methodsmentioning
confidence: 99%
“…The JACSIS gathers data from the pooled panels of an internet research agency (Rakuten Insight, Inc. [https://insig ht.rakut en.co.jp/], which has approximately 2.3 million panelists currently); details of the JACSIS, quality controls, and other policies for panelists have been described previously. 6,19,20 Briefly, the JACSIS consists of three internet-based survey panels of (a) young people and adults aged 15-79 years, (b) pregnant/postpartum mothers and fetus/infant pairs, and (c) adults living in a single-parent household. In this study, we exclusively used data from the panel of postpartum mother-infant pairs, in which the age and geographical distributions were nationally representative.…”
Section: Study Design Data Setting and Participantsmentioning
confidence: 99%
“…The sample size of 1,000 was decided based on feasibility to conduct the research. Details of the sampling strategy are described elsewhere ( Okawa et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%